Las relaciones bilaterales entre Ecuador China: factor estratégico de los lineamientos en las políticas de defensa de las Fuerzas Armadas Ecuatorianas durante el periodo 2009-2015 - Criollo Asimbaya, Marco Antonio (2017)
The present research work "The bilateral relations between Ecuador and China: Strategic factor of the guidelines in the policies of Defense of the Ecuadorian Armed Forces during the period 2009-2015”, Contextualizes the power relations maintained by the States, to define a logic of cooperation according to their interests, capacities and vulnerabilities of their realities, which are aligned with the establishment of bilateral ties, agreements and conventions as implemented by Ecuador and China. The application of the Foreign Policy instruments and the theories of international relations allow us to delimit the present investigation, focused directly on the reality of the Ecuadorian State, and to its strategic partner China, in which case relations begin from 1980, Increasing its application during the years 2009 to 2015. In this same order of ideas, the study proposal takes as a reference the theoretical content of complex interdependence, as the basis of the relations of States and their members, in which it contextualizes the military as one more component of a State, but that does not necessarily have a preponderant importance as it had previously.